AN ANALYSIS OF MORAL VALUES OF THE DRAMA SERIES YUMI'S CELL - Fitriana Hidayanti (Airlangga Development Journal, 2023)
The purpose of the study is to analyze and describe the moral values in Yumi's Cells drama series. The type of research is descriptive qualitative with content analysis techniques. Study found that there are moral values contained in the drama series, namely the importance of being disciplined, frugal, not adhering to negative thoughts, being helpful, thinking rationally, being professional, wise, calm, polite, honest, mindful, loving of ourselves, and being resilient. Other moral values are about sacrifices, keeping in touch, being open, courageous, and to apologize, to be ready for the worst, being independent, hygienic, responsible, and hardworking. The drama series with a cinematography that combined 3D animation and live action is recommended to be watched by teenagers and adult because the moral values contained in the series are in accordance with Indonesian culture.